Optimising the performance of frontline implementers engaged in the NTD programme in Nigeria: lessons for strengthening community health systems for universal health coverage - Akinola Oluwole; Laura Dean; Luret Lar; Kabiru Salami; Okefu Okoko; Sunday Isiyaku; Ruth Dixon; Elizabeth Elhassan; Elena Schmidt; Rachael Thomson; Sally Theobald; Kim Ozano (BMC, 2019)
Abstract Background The control and elimination of Neglected Tropical Diseases (NTDs) is dependent on mass administration of medicines (MAM) in communities and schools by community drug distributers (CDDs) who are supported and supervised by health facility staff (FLHF) and teachers. Understanding how to motivate, retain and optimise their performance is essential to ensure communities accept medicines. This study aimed to capture and translate knowledge, problems and solutions, identified by implementers, to enhance NTD programme delivery at the community level in Nigeria. Methods Qualitative data was collected through participatory stakeholder workshops organised around two themes: (i) identification of problems and (ii) finding solutions. Eighteen problem-focused workshops and 20 solution-focussed workshops were held with FLHF, CDDs and teachers in 12 purposively selected local government areas (LGA) across two states in Nigeria, Ogun and Kaduna States. Result The problems and solutions identified by frontline implementers were organised into three broad themes: technical support, social support and incentives. Areas identified for technical support included training, supervision, human resource management and workload, equipment and resources and timing of MAM implementation. Social support needs were for more equitable drug distributor selection processes, effective community sensitisation mechanisms and being associated with the health system. Incentives identified were both non-financial and financial including receiving positive community feedback and recognition and monetary remuneration. The results led to the development of the 'NTD frontline implementer's framework' which was adapted from the Community Health Worker (CHW) Generic Logic Model by Naimoli et al. (Hum Resour Health 12:56, 2014). Conclusion Maximising performance of frontline implementers is key to successful attainment of NTD goals and other health interventions. As NTDs are viewed as a 'litmus test' for universal health coverage, the lessons shared here could cut across programmes aiming to achieve equitable coverage. It is critical to strengthen the collaboration between health systems and communities so that together they can jointly provide the necessary support for frontline implementers to deliver health for all. This research presents additional evidence that involving frontline implementers in the planning and implementation of health interventions through regular feedback before, during and after implementation has the potential to strengthen health outcomes.